Habits and nutrition knowledge of adolescent performance swimmers - M. Ocaña; R. Folle; C. Saldaña (Asociación Española de Ciencias del Deporte, 2010)
The aim of this study was to assess the general eating habits and the nutritional knowledge of a group of adolescent performance swimmers. 20 swimmers (10 men, 10 women, mean age: 14.85 years, SD = 1.5) and 20 controls performance sport activities (11 men, 9 women, average age: 14.50 years, SD =0.68) participated in this study. Nutritional Knowledge Questionnaire (Bach, 2003), Knowledge and Attitudes on Nutrition Questionnaire (Zawila, 2003) and an adaptation of the Lifestyles Project OBA questionnaire (cf. Sánchez-Carracedo and Saldaña, 1998 ) were used. The results showed that swimmers had an average nutrition knowledge and they were generally better informed about nutrition (p <0001) and nutrition for the athlete (p = 0063) than their controls, meanwhile dietary habits of the two groups were similar. Dietary habits of swimmers must be oriented. It is necessary to promote the role of coaches as informants on nutrition. Key Words:dietary habits, nutritional knowledge, swimmers, adolescents